1989
DOI: 10.3382/ps.0680608
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Time and Body Temperature Interactions in Broiler Breeders

Abstract: Four groups of 70-wk-old broiler breeder females were fed once daily at 0600, 1000, 1400, and 1800 h to determine the effect of feeding time and eating on body temperature. The photoperiod was from 0430 to 1930 h. Four floor pens of 30 hens each were assigned per feeding time. Following a 9-day adjustment period, body temperature was determined, in series, by rectal probe of 5 birds/pen at 7 and 3 h prefeeding and 1, 5, 9, and 13 h postfeeding. Body temperature was increased .5 C at 1 h postfeeding in all grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
5
8
0
Order By: Relevance
“…Kohne et al (1973, reported that feeding time should be considered at high environmental temperature due to the caloric increment produced by exothermic reactions of nutritional metabolism. Heat increment was higher 5 h after feeding in birds fed at 6:00 am than in birds fed at 2:00 pm when indoor temperature increased (Wilson et al, 1989).…”
Section: Introductionmentioning
confidence: 88%
“…Kohne et al (1973, reported that feeding time should be considered at high environmental temperature due to the caloric increment produced by exothermic reactions of nutritional metabolism. Heat increment was higher 5 h after feeding in birds fed at 6:00 am than in birds fed at 2:00 pm when indoor temperature increased (Wilson et al, 1989).…”
Section: Introductionmentioning
confidence: 88%
“…Because food ingestion is associated with an acute rise in body temperature in various species (197,245,(320)(321)(322), and because animals and humans tend to eat mostly at certain times of the day (323,324), it is conceivable that the CRT could be a mere side-effect of the circadian rhythm of food consumption. That is, in animals fed ad libitum, the concentration of feeding during the light phase or the dark phase of the light-dark cycle could possibly result in the chronic elevation of body temperature that characterizes the CRT.…”
Section: Food Availabilitymentioning
confidence: 99%
“…However, there have been several studies conducted under constant light and under relatively stable conditions of ambient temperature and feeding. In chicken kept under constant light, a clear circadian rhythm of body temperature was observed (47,51,52). The closest estimate of the endogenous free-running period (23.5 h) is provided by a study in which roosters were maintained under dim constant light (52).…”
Section: Endogenous and Exogenous Determinantsmentioning
confidence: 99%